2013
DOI: 10.1186/1477-7819-11-142
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian granulosa cell tumors: a retrospective study of 27 cases and a review of the literature

Abstract: BackgroundGranulosa tumors were described for the first time in 1855 by Rokitansky. These tumors are malignancies with a relatively favorable prognosis. They are characterized by a prolonged natural history and a tendency to late recurrences. The aim of this study is to investigate the epidemiological and pathological characteristics of granulosa cell tumors and to investigate the prognosis factor for recurrences.MethodsThe clinical data of patients who were treated in the period from January 2003 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 32 publications
4
63
0
1
Order By: Relevance
“…6 The serum tumor markers are inhibin, estradiol and anti mullerian hormone. 7 The Serum CA125 is not associated with tumor progression. 7 Mutation in FOXL2 gene has been identified in 97% of adult granulosa cell tumor and 10 percentage of juvenile granulosa cell tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The serum tumor markers are inhibin, estradiol and anti mullerian hormone. 7 The Serum CA125 is not associated with tumor progression. 7 Mutation in FOXL2 gene has been identified in 97% of adult granulosa cell tumor and 10 percentage of juvenile granulosa cell tumor.…”
Section: Discussionmentioning
confidence: 99%
“…However, late relapse often occurs due to an indolent disease course, and the prognosis of advanced disease is poor, with a 5-year survival rate of 0% to 20%, comparable to that for epithelial ovarian cancer. 4 Prognostic factors for Granulosa Cell tumours have been reported previously and include age, tumor size, tumor rupture, tumor stage, bilaterality, postoperative residual tumour status and high mitotic index (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, prognostic factors for Granulosa Cell tumour and it's recurrent nature remain unclear, due to rarity and indolent course of the disease.…”
Section: Mostmentioning
confidence: 99%
“…They are characterized by a prolonged natural history and a tendency to late recurrences. 2 Kalfa et al identified a mutation FOXL2 (transcription factor gene) in the majority of GCTs, particularly in adult form. This FOXL2 could be the next target for use in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal bleeding, hirsutism, and often virilization are the main clinical manifestations, whereas malignant transformation has been reported in very few cases (59). Primary granulosa cell tumors account for 2-3% of all ovarian tumors and are mostly found during the sixth decade of life (67). Although the majority are diagnosed at an early stage (stage I) and thus exhibit a good prognosis, late recurrences and dissemination necessitating systemic chemotherapy may occur.…”
Section: Androgen-secreting Ovarian Tumorsmentioning
confidence: 99%
“…Although the majority are diagnosed at an early stage (stage I) and thus exhibit a good prognosis, late recurrences and dissemination necessitating systemic chemotherapy may occur. Granulosa cell tumors mainly secrete estrogens leading to postmenopausal bleeding, endometrial hyperplasia, and endometrial carcinoma; however, w10% may secrete androgens and cause virilization (67,68). In addition to estradiol and testosterone, inhibin and anti-Müllerian hormone can be used as specific tumor markers for granulosa and Sertoli cell ovarian tumors (69,70).…”
Section: Androgen-secreting Ovarian Tumorsmentioning
confidence: 99%